CFD simulation design and optimization of a novel zigzag wave-plate mist eliminator with perforated plate. (5th February 2021) - Fang, Can; Zou, Renjie; Luo, Guangqian; Ji, Qingyu; Sun, Ruize; Hu, Hongyun; Li, Xian; Yao, Hong
Highlights: Zigzag wave-plate mist eliminator with the perforated plate was proposed. Three evaluation indicators were investigated by the CFD simulation method. The particle trapping process on the perforated plate was studied numerically. The perforated plate can be processed and manufactured by integrated technology. Abstract: A zigzag wave-plate mist eliminator with an internally improved structure of perforated plate was proposed in this work, which applied in particle removal process for lime-stone wet flue desulfurization (WFGD) system. Its performance was evaluated by Computational Fluid Dynamics (CFD) methods with three criteria, overall collection efficiency, system pressure drop, and impact factor. The realizable k - ε turbulence model and Eulerian-Lagrangian methodology were adopted to describe the motion of the continuous phase and dispersed phase. The CFD results showed that the main factors affecting the performance of perforated plate mist eliminator are the number of perforated plates N, the perforated plate interval spacing I, the hole diameter d 1, the distance between two holes d 2, porosity ε, installation angle α, and the height of the perforated plate h . Compared with the wave-plate mist eliminator with porous foam layers, the mist eliminator with perforated plate is found to have better performance in particle removal. The overall particle collection efficiency is increased by more than 2.3%, the pressure drop is reduced by more than 27.4% while the porosity of the perforated plate is small. When ε is large, the particle collection efficiency of the porous plate with large porosity decreased by 0.3–1.2%, the pressure drop was reduced by more than 34.7%. Besides, it has a simple structure and can be processed by integrated technology. All these advantages make the perforated plate mist eliminator a promising candidate for fine particle removal in the WFGD system.